PENGGUNAAN BIJI NANGKA DALAM PEMBUATAN EDIBLE FILM DENGAN PENAMBAHAN KITOSAN - Mutia Amran; Indang Dewata (Jurnal Kependudukan dan Pembangunan Lingkungan, 2021)
Edible film is a fil or thin layer with a thickness of less than 0.25 mm which is useful as a protect food products. This study aims to determine the effect of adding chitosan to edible film made from jackfruit seed starch on the mechanical properties and biodegradation of edible films. The addition of variation in the concentration of chitosan as much as 0%, 0.5%, 1%, 1.5% and 2%. Based on the results of the analysis of the data obtained, it is stated that the adition of chitosn affects the thickness, tensile strength and biodegradation of the edible films. The maximum tensile strength was obtained with the addition of 1% chitosan concentration of 13.9 Mpa. The tickness of the edible film increases with the addition of the concentration of chitosan, while the biodegradation of the edible film decreases with the addition of the concentration of chitosan.